Kształtowanie samoświadomości moralnej małżonka w nauczaniu św. Augustyna z Hippony - Swoboda, Antoni (Poznańskie Studia Teologiczne, 2013)
The article is divided into two paragraphs. The first paragraph presents St. Augustine’s opinion on the husband as a person. His remarks on the appearance as well as the personal values of a man and husband are discussed. The second paragraph deals with the issue of personality formation, including such points as the care to form moral goodness, especially the virtues of chastity and continence. This paragraph also considers St. Augustine’s view on concupiscence. The bishop of Hippo not only assesses concupiscence but also gives encouragement to overcome it and at the same time suggests methods that enable its control. Keywords